High resolution para-hydrogen induced polarization in inhomogeneous magnetic fields - Buljubasich Gentiletti, Lisandro (2013)
The application of parahydrogen for the generation of hyperpolarization has increased continuously during the last years. When the chemical reaction is carried out at the same field as the NMR experiment (PASADENA protocol) an antiphase signal is obtained, with a separation of the resonance lines of a few Hz. This imposes a stringent limit to the homogeneity of the magnetic field in order to avoid signal cancellation. In this work we detect the signal arising from hyperpolarized Hexene by means of a CPMG pulse train. After Fourier transformation the obtained J-spectra not only presents an enhanced spectral resolution but also avoids partial peak cancellation.